Relationship between Anterior Cruciate Ligament Injury and Flat-Foot among Volleyball Players of Lahore, Pakistan - Sana Tauqeer, Muhammad Adnan, Ammarah Ikram, Ayesha Aslam Sapra, Umer Rafique, Assra Noor Javed, Hammad Shakeel, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A person with flat feet experiences a decrease in their medial arch when they bear weight. Players of volleyball are more vulnerable to ACL problems. Playing volley-ball increases the risk of ACL damage because of the repeated jumping and falling on the ground. Aim: To find relationship between anterior cruciate ligament injury and flat-feet among volleyball players of Lahore, Pakistan Methodology: This cross-sectional study included volley-ball players and was conducted on 158players. Participants were selected by non-probability sampling. Their age was in range between20 to30 years and only males were included. For collection of data KUJALA score (anterior knee pain scale) was used to assess anterior cruciate ligament injury and Clarke’s angle was used to measure flat-foot. Data was collected from training academies in Lahore. Written consent was taken from the participants and the significance of the study were explained before filling the questionnaires. Results: In present study the mean age was 23.14. The mean of KUJALA score and Clarke’s angle for right knee and flat foot was 77.78 and 9.57 respectively. The mean of KUJALA score and Clarke’s angle for left knee and flat foot was 71.90 and 9.09 respectively. The Pearson’s correlation showed negative correlation between KUJALA score and Clarke’s angle. Practical Implications: This research will be very beneficial to society it will help to make a correct and beneficial rehabilitation plan for flat foot patients having ligamentous injury. It will also help athletes to decrease pain management for patients having ACL injury in flat foot patients. Conclusion: The present study concluded that there is negative correlation between anterior cruciate ligament injury and flat foot which means reduction in medial longitudinal arch can increase knee pain followed by anterior cruciate ligament injury. Keywords: Anterior cruciate ligament, Athletes, Flat foot, Volleyball players